Analisis Tingkat Kepuasan Pustakawan Pada Perpustakaan Menggunakan Pieces Framework - Diah Amelia; Sanjaya Pinem; Syafriyandi Syafriyandi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
This study aims at OPAC implementation effect in digital library from the user perspectiveusing PIECES analysis. The object of this research is the library in State Polytechnic of MediaKreatif. Observation, questionnaires, and interviews were used to collect data. Observations areused to see how the existing system works physically, questionnaires are used to collect data thatwill be analyzed further, and interviews are used to support observation and interviews. The dataanalysis technique used in this library research uses descriptive statistical analysis with the averageresults from the PIECES Framework. The results of the study using the PIECES frameworkanalysis found that the performance variable (4.64), information variable (4.35), economy variable(3.47), control variable (3.97), efficiency (4.11), and services (3,83).